Climate-smart management can further improve winter wheat yield in China. (May 2018) - Sun, Shuang; Yang, Xiaoguang; Lin, Xiaomao; Sassenrath, Gretchen F.; Li, Kenan
Abstract: Climate change, genotype, and agronomic management have profound impacts on crop yield. Our goal in this study is to untangle the interrelated contributions of climate change, genetic improvements, and agronomic management on winter wheat yield in China to develop management strategies that address future nutritional needs. The Agricultural Production System Simulator (APSIM) farming systems model was used to simulated long-term (1981–2010) wheat yield for four wheat production regions under different Genotype by Environment by Management (GxExM) scenarios. Using detailed field experimental data from 1981 to 2005 in conjunction with the APSIM-wheat model, the potential for climate-smart management to improve yield on a regional scale is investigated. Results showed that when all climatic variables were considered together, winter wheat relative yield change decreased from 0.62% to 7.16% over the period 1981 to 2010, depending on cultivar and growing region. The impact of individual climatic variables varied by region. In general, winter wheat yields showed the least decline in the Northern China Plain (NC) due to climate change. Cultivar renewal combined with improvements in agronomic management boosted yields but to a different extent in each region. For cultivar renewal, yields increased 6.93%, 17.69%, 24.87%, and 52.72% in the NC, Yellow and Huai River Valleys (YH), SW and YV, respectively over the period 1981 to 2010. Agronomic management improved yields by 22.91%, 5.27%, 58.77%, and 59.20% in these regions, respectively. Overall, the observed yield improvements with agronomic management were higher than those resulting from cultivar renewal for most of China's wheat growing regions. The exception was found in YH, where improvements in winter wheat yield from cultivar renewal were greater than those from agronomic management. Regardless, there is still ample room for yield improvement in winter wheat by implementing climate-smart management. SW would benefit significantly, with a potential increase of 99% because of improved agronomic management. More moderate, but still significant increases were predicted for NC and YH (49% and 42%, respectively) while only moderate improvements were anticipated for YV (17%). Our findings highlight the extent that improvements in cultivar renewal and agronomic management have compensated for the negative impacts of climate change for different wheat growing regions of China over the past three decades. The results also indicate that advances in agronomic management outweighed the effects of cultivar renewal in most regions. Climate-smart management is still needed to further improve yields in wheat-growing regions of China. Highlights: Yields showed the least decline in the Northern China Plain due to climate change. Advances in cultivar and agronomic practice boosted yields but varied by regions. Improvements in agronomic management outweighed cultivar renewal in most regions. Climate-smart management is still needed to further improve winter wheat yield.